Perkembangan Dan Strategi Bisnis Coffee Shop di Era Modern: Studi Kasus Pada Coffee Shop Lokal di Indonesia - Muhammad Wildan; Muhammd Irfan; Rendi David Sanjaya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Coffee shop Coffee shops are no longer just places to drink coffee, but have evolved into social spaces, lifestyles, and informal workplaces. This study aims to explore the business and marketing strategies used by local coffee shops in Indonesia, and analyze the factors that influence their success amidst competition with big brands and international franchises. The research method uses a descriptive qualitative approach with semi-structured interviews, field observations, and digital documentation. The study was conducted in three major cities (Jakarta, Bandung, and Yogyakarta) with the main subjects being local coffee shop owners and managers. The data analysis technique uses a thematic approach to explore digital promotion strategies, menu innovation, interior design, and customer experience. The results of the study show that the success of local coffee shops is determined by the ability to adapt to trends, emotional connections with customers, the strength of brand image, and the use of social media creatively and consistently. Important findings also show that collaboration with the local community, personal service, and Instagrammable aesthetic design play a major role in creating customer loyalty. The SWOT analysis confirms that the main strength lies in innovation and relationships, although there are still challenges in terms of business scale and competition with big franchises. This study concludes that local coffee shops that are able to create emotional and social experiences for customers have a great opportunity to survive and develop sustainably in the competitive digital era.